Performance Analysis Of Standart Camshaft Engines And Modified Camshafts On 110cc Motorcycles - Muhammad Derrio; Aser Eben Ezer Sihombing; Jumiati Ratuloli; Fardin Hasibuan (Universitas Riau Kepulauan, 2025)
Currently, motorcycles are the maximum extensively used approach of transportation in Indonesia. apart from being a way of transportation and for delivering items, of direction, it has unique settings from motorbikes which might be used for daily purposes via making overall performance upgrades by using modifying the noken axle (camshaft) on motorbikes which are used each day. The characteristic of the camshaft is to manipulate the valve opening, both the consumption and exhaust valves at the time decided with the aid of the four stroke engine cycle. at the changed engine, numerous adjustments have been made to several systems and components to improve the performance of the bike. The cause of this take a look at become to determine the performance of the Honda Absolute revo 110cc combustion engine which incorporates torque, strength and gasoline intake with the aid of comparing the standard camshaft and The changed camshaft which has modified the lift top by using 1mm has changed in the absolute revo 110cc engine, adjustments occur amongst them in torque, energy and greater gasoline intake enter the combustion chamber. The studies was received from a tool which can decide power called Dynotest. Dynotest serves to measure the torque strength of a motorcycle that has been modified by means of camsaft so as to understand better which is the modified camasafth and the usual camsafth on a 110cc revo absolute motorcycle.